(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
The transport systems operating within the city in general and its center in particular have a great impact on urban development within the city’s sustainability. Development in all its parts and components aims at preserving the human, environment and resources on the one hand and providing a safe, easy and healthy life on the one hand. Transport is a fundamental, effective and effective part of development because of its great impact on the development of cities. Today, it is the basis of the engine of life in cities and its impact on the economic, tourism, social, environmental and many more. Traffic systems during the last century, and continuing to come together now and in the future, and is a natural consequence of the substantial increase in population numbers throughout the world, including Baghdad city center. Therefore, the importance of the subject is "the result of the importance of transport systems operating in the city and its impact on development and the environmental, economic and health aspects." The hypothesis "Integrated and sustainable public transport systems have social, environmental, health and economic impacts at the city level in general, Access when available "research problem" is the lack of a clear cognitive perception of the reality of the transport systems adopted in the city on development and the environmental, economic, social and health.